2021
DOI: 10.3390/agronomy11030571
|View full text |Cite
|
Sign up to set email alerts
|

NaCl- and Na2SO4-Induced Salinity Differentially Affect Clay Soil Chemical Properties and Yield Components of Two Rice Cultivars (Oryza sativa L.) in Burundi

Abstract: Salinity may strongly influence the interaction between plant roots and surrounding soil, but this has been poorly studied for sodium sulfate (Na2SO4). The aim of this study was to investigate the effect of sodium chloride (NaCl) and Na2SO4 salinities on the soil chemical properties as well as rice physiological- and yield-related parameters of two contrasted cultivars (V14 (salt-sensitive) and Pokkali (salt-resistant)). Pot experiments were conducted using soil and electrolyte solutions, namely NaCl and Na2SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…1 ). This was in accordance with the study by Irakoze et al (2021) , where rice yield decreased by 50% when being applied with 3‰ saline water. As demonstrated by Aguilar et al (2017) , applying saline water at the vegetative stage of rice lowered plant height, number of panicles, 1,000-seed weight, number of filled seeds, harvest index, and grain yield due to the osmosis and toxicity of Na + ion ( Mensah et al, 2006 ; Rengasamy & Olsson, 1993 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1 ). This was in accordance with the study by Irakoze et al (2021) , where rice yield decreased by 50% when being applied with 3‰ saline water. As demonstrated by Aguilar et al (2017) , applying saline water at the vegetative stage of rice lowered plant height, number of panicles, 1,000-seed weight, number of filled seeds, harvest index, and grain yield due to the osmosis and toxicity of Na + ion ( Mensah et al, 2006 ; Rengasamy & Olsson, 1993 ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, acidity adversely affects the growth and the capability of accumulating nutrients of the plants ( Huang et al, 2017 ; Tsai & Schmidt, 2021 ). Furthermore, high Na + concentration also interferes with the process of taking nutrients and the growth of rice ( Irakoze et al, 2021 ; Syed et al, 2021 ), while rice is one of the major crops in Vietnam, whose soil has been damaged by salinity and acidity. In the current study, the soil salinity was positively correlated with the saline levels in the water applied for rice cultivation, shown via the EC value and the amount of exchanging Na + in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increasing problems that soil and irrigation water salinization poses to global crop production, there is an urgent need to propose sustainable and cost-effective practices that may alleviate its negative effects on plant growth, crop performance and final product quality. In this context, the aim of this study was to determine the effect of nutrient solutions (NSs) with high EC levels (8.5 dS m −1 ) [29,30] due to high minerals or high NaCl concentrations on the growth and development of Pelargonium graveolens and Verbena officinallis plants grown in a soilless (perlite substrate) cultivation system.…”
Section: Introductionmentioning
confidence: 99%
“…Salt stress induces a double constraint on plants: i) an osmotic constraint related to the decrease in the external osmotic potential and ii) an ionic constraint related to the accumulation of Na and Cl − ions (Castillo et al, 2007;Ben Hassine and Lutts, 2010;Qin et al, 2020). Although nutrient solutions are frequently used to study the impact of NaCl on plants, the present work was conducted on soil substrate assuming that soil properties may have an impact on root behavior in relation to ion bioavailability, but also that salinity may affect the soil structure as recently demonstrated in O. sativa (Irakoze et al, 2021). The chemical analysis of the selected soil demonstrated that it is a neutral soil with low organic carbon and total nitrogen content (Table 1).…”
Section: Discussionmentioning
confidence: 99%